TRIM21 and PHLDA3 negatively regulate the crosstalk between the PI3K/AKT pathway and PPP metabolism - Jie Cheng (Nature Portfolio, 2020)
The PI3K/AKT signalling pathway regulates cancer metabolism. Here, the authors show a reciprocal positive feedback crosstalk between the PI3K/AKT and pentose phosphate pathway which promotes tumourigenesis.